Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Cách 1: y' = (9 -2x)'(2x3- 9x2 +1) +(9 -2x)(2x3- 9x2 +1)' = -2(2x3- 9x2 +1) +(9 -2x)(6x2 -18x) = -16x3 +108x2 -162x -2.
Cách 2: y = -4x4 +36x3 -81x2 -2x +9, do đó
y' = -16x3 +108x2 -162x -2.
b) y' = .(7x -3) +
(7x -3)'=
(7x -3) +7
.
c) y' = (x -2)'√(x2 +1) + (x -2)(√x2 +1)' = √(x2 +1) + (x -2) = √(x2 +1) + (x -2)
= √(x2 +1) +
=
.
d) y' = 2tanx.(tanx)' - (x2)' =
.
e) y' = sin
=
sin
.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(dy=d\left(\dfrac{\sqrt{x}}{a+b}\right)=\left(\dfrac{\sqrt{x}}{a+b}\right)dx=\dfrac{1}{2\left(a+b\right)\sqrt{x}}dx\)
b) \(dy=d\left(x^2+4x+1\right)\left(x^2-\sqrt{x}\right)=\left[\left(2x+4\right)\left(x^2-\sqrt{x}\right)+\left(x^2+4x+1\right)\left(2x-\dfrac{1}{2\sqrt{x}}\right)\right]dx\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a) y' = =
, y" =
=
=
.
b) y' = =
;
y" = =
=
.
c) y' = ; y" =
=
=
.
d) y' = 2cosx.(cosx)' = 2cosx.(-sinx) = - 2sinx.cosx = -sin2x,
y" = -(2x)'.cos2x = -2cos2x.
a) y' = 2x -
= 2x -
.
b) y' =
=
.
c) y' =
=
=
=
.
d) y' =
=
=
=
.